Space Imaging of Six-Wave Mixing in a Rydberg Dressing Atomic Ensemble - Junling Che; Jintao Bai; Yanpeng Zhang (IEEE Photonics Journal)
Atoms excited to Rydberg states can be used to enhance the nonlinearity of medium via electromagnetic induced transparency (EIT) due to their special property. In this letter, focusing on a Rydberg medium with strong nonlinearity, we investigate the space imaging characteristics of generating Rydberg EIT-assisted six-wave mixing in a K-type five-level atomic system. Rydberg spatial image variation regularity modulated by an optical field was obtained. This study on the regulation of image variation was able to establish a relation between the refractive index of the Rydberg medium and optical field, which will not only expand research on Rydberg space optical phenomena but can also provide the basis for advanced designs that are highly dependent on the refractive index materials. More importantly, these results have research value in the field of optical information processing.